2022
DOI: 10.1101/2022.01.24.22269714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccines effectiveness against symptomatic SARS-CoV-2 during Delta variant surge: a population-based case-control study in St. Petersburg, Russia

Abstract: Background: Studies of mRNA and vector-based vaccines used in different countries report acceptable levels of effectiveness against SARS-CoV-2 infection caused by the Delta variants of SARS-CoV-2. No studies estimated vaccine effectiveness (VE) of Gam-COVID-Vac and other vaccines used in Russia against symptomatic infection with Delta variant. In this population-based case-control study, we aimed to estimate the effectiveness of the Russian COVID-19 vaccines against symptomatic SARS-CoV-2 during the recent out… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(33 reference statements)
3
8
0
Order By: Relevance
“…We find that the estimated VE of the Sputnik V vaccine to prevent deaths and severe forms of disease caused by the Delta variant of SARS-CoV-2 is comparable to the estimated VE of this vaccine against COVID-19 caused by other viral variants that have previously appeared in circulation. Our observations are consistent with other studies that have evaluated the VE of Sputnik V in clinical trials [ 6 ] or case-control studies [ 41 ]. However, due to several factors, and primarily due to the limitations of the database with which we worked, it was impossible to directly compare the estimated VE values in our work with VE estimates from published papers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We find that the estimated VE of the Sputnik V vaccine to prevent deaths and severe forms of disease caused by the Delta variant of SARS-CoV-2 is comparable to the estimated VE of this vaccine against COVID-19 caused by other viral variants that have previously appeared in circulation. Our observations are consistent with other studies that have evaluated the VE of Sputnik V in clinical trials [ 6 ] or case-control studies [ 41 ]. However, due to several factors, and primarily due to the limitations of the database with which we worked, it was impossible to directly compare the estimated VE values in our work with VE estimates from published papers.…”
Section: Discussionsupporting
confidence: 93%
“…To date, the developers of EpiVacCorona have not published the results of their phase III study. The results of this analysis, along with an earlier analysis [ 41 ], indicate a lack of protective VE. Our study showed the negative efficacy of EpiVacCorona.…”
Section: Discussionsupporting
confidence: 61%
“…However, in its response to an inquiry by a member of St. Petersburg Legislative Assemblу city Health Committee revealed that, by July 23, 2021, in St. Petersburg, among 1,227,496 individuals who received at least one vaccine dose, 1,178,266 or 96% received GamCOVIDVac, and the rest is distributed between the other two vaccines (EpiVacCorona -21,943 or 1.7% and KoviVac 27,287 or 2.2%) [19]. October 2021 survey showed that only about 10% of responders in St. Petersburg received a vaccine other than GamCOVIDVac [22]. It is safe to assume that our study approximates the effectiveness of GamCOVID Vac.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of vaccinated residents in St. Petersburg received Gam-COVID-Vac. The proportion of the population that received other vaccines was 10% or less in St. Petersburg [19, 22].…”
Section: Methodsmentioning
confidence: 99%
“…The true immunogenicity of EpiVacCorona appeared to be lower than declared (70% versus the 100% claimed in official statements). Moreover, as a preprint stated, “immunisation with this vaccine did not lead to emergence of neutralising antibodies in healthy volunteers.” Two further1011 preprints have since been issued (one by a group of epidemiologists from St Petersburg, the other by a scientist and a science journalist), both claiming negative efficacy for EpiVacCorona. This could also be because of the small size of the cohort studied, or because of the tendency in vaccinated people to be less cautious about spreading infection, preprint authors suggested.…”
Section: Data Scrutinymentioning
confidence: 99%